Government expenditures and unemployment: A DSGE perspective - Eric Mayer; Stéphane Moyen; Nikolai Stähler (Deutsche Bundesbank, 2010)
In a New Keynesian DSGE model with labor market frictions and liquidity-constrained consumers aggregate unemployment is likely to increase due to a non-persistent government spending shock. Furthermore, the group of asset-holding households reacts very differently from the group of liquidity-constrained consumers implying that the unemployment rate is likely to decrease for asset-holding households, while it increases among liquidity-constrained consumers. The main driver of our results is the marginal utility of consumption which moves in opposite directions for the two types. Regarding the model's parameters, we find that the size of the fiscal (unemployment) multiplier increases with i) highly sticky prices, ii) high degrees of risk aversion, iii) low convexity in labor disutility iv) high replacement rates, and v) debt-financed expenditures.
Keywords: E32; J64; E62; 330; Search and matching; government spending shocks; unemployment; Öffentliche Ausgaben; Schock; Multiplikator; Arbeitslosigkeit; Ungleichgewichtstheorie; Dynamisches Gleichgewicht; Verschuldungsrestriktion; Arbeitsmarkttheorie; Matching; Theorie